The effect of constant or variable forage to concentrate ratio in total mixed ration on performance of primiparous dairy cows - Mäntysaari, Päivi; Nousiainen, Juha; Huhtanen, Pekka (Elsevier, 2003)
The performance of 45 primiparous Ayrshire cows fed total mixed ration (TMR) with constant (TMR1) or variable (TMR3) proportion of concentrate in dry matter was studied. On TMR1 treatment the forage to concentrate ratio of TMR was 53:47 in dry matter (DM) throughout the lactation. On TMR3 the forage to concentrate ratio increased during the lactation being 43:57, 53:47 and 63:37 on 0 100, 101 200 and 201 305 days post partum, respectively. The experimental period was 305 days of the first lactation. The feeding strategy had no significant effect on average milk yield. The energy corrected milk yield was 24.4 kg/day on TMR1 and 24.3 kg/day on TMR3 treatment. Also milk protein content was not affected by the treatment, but the milk fat content tended (P<0.09) to be higher on TMR1 treatment. The average DM intake was not different between treatments (16.7 vs. 17.1 kg/day). However, reflecting the milk yield also the daily feed intake was positively correlated with the proportion of concentrate in the ration. No significant difference in feed conversion ratio was measured. Feeding a constant forage to concentrate ratio through out the lactation did not cause fattening of the primiparous cows in late lactation. Overall, the results indicate no difference in the performance of primiparous cows fed TMR with constant or variable forage to concentrate ratio in the diet.
Keywords: Ko; lypsykarja; ruokinta; maitotuotos; dairy cattle; feeding; milk yield; feeding strategy; total mixed ration